Chronic Lateral Ankle Instability: Topical Review. (December 2020) - Aicale, Rocco; Maffulli, Nicola
Chronic ankle instability can result from untreated or badly managed acute lateral ankle ligament injuries. Conservative management is the modality of choice for acute lateral ankle ligament injuries, and operative treatment is reserved for special cases. Failure after strict rehabilitation may be an indication for surgery. Several operative options are available, including anatomic repair, anatomic reconstruction, and tenodesis procedures. Anatomic repair can be performed when the quality of the damaged ligaments permits. Anatomic reconstruction with an autograft or allograft should be considered when the torn ligaments are not adequate. Ankle arthroscopy is a useful adjunct to ligamentous procedures, performed at the time of repair to identify and treat intra-articular conditions that may be associated with chronic ankle instability. Tenodesis techniques are not recommended because of their suboptimal long-term results related to the modification of ankle and hindfoot biomechanics. Level of Evidence: Level V, expert opinion.